2018
DOI: 10.1155/2018/6368309
|View full text |Cite
|
Sign up to set email alerts
|

MultiParametric Magnetic Resonance Imaging-Based Nomogram for Predicting Prostate Cancer and Clinically Significant Prostate Cancer in Men Undergoing Repeat Prostate Biopsy

Abstract: Objective To develop and internally validate nomograms based on multiparametric magnetic resonance imaging (mpMRI) to predict prostate cancer (PCa) and clinically significant prostate cancer (csPCa) in patients with a previous negative prostate biopsy. Materials and Methods The clinicopathological parameters of 231 patients who underwent a repeat systematic prostate biopsy and mpMRI were reviewed. Based on Prostate Imaging and Reporting Data System, the mpMRI results were assigned into three groups: Groups “ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Relatively higher rates of PCa on repeat biopsy, ranging from 20% to 34%, have been reported by previous studies. [3][4][5] However, the criteria or indications for making a decision to perform a repeat biopsy procedure are not well defined. The AUC of models constructed by traditional clinical parameters in the repeat biopsy is only approximately 70%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively higher rates of PCa on repeat biopsy, ranging from 20% to 34%, have been reported by previous studies. [3][4][5] However, the criteria or indications for making a decision to perform a repeat biopsy procedure are not well defined. The AUC of models constructed by traditional clinical parameters in the repeat biopsy is only approximately 70%.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the 20 to 40% false-negative rate of the initial biopsy and persistent abnormal clinical-pathological parameters more than 50% of patients who undergo initial biopsy are left with doubt regarding the potential presence of PCa and need repeat biopsy after a period of follow-up. [2][3][4][5] Despite the numbers of traditional clinical-pathological parameters, including prostate-specific antigen (PSA), percentage of free-PSA (fPSA), PSA velocity, and presence of high-grade prostatic intraepithelial neoplasia (HGPIN) or atypical small acinar proliferation (ASAP) in the previous negative biopsy tissues were used to screen patients for repeat biopsy, unfortunately, the positive biopsy rate among men undergoing repeat biopsy is only approximately 20% to 40% and high grade PCa (HGPCa) accounted for less than half, which suggests that three out of every five biopsies are unnecessary. [2][3][4][5][6] Prostate biopsy can be painful, anxiety-provoking, expensive, and potentially morbid, so there is an urgent need to supplement the above mentioned traditional parameters with novel biomarkers that enhance its specificity so that unnecessary biopsies can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [27] developed an MRI risk prediction model, based on age, PSA, prostate volume, and DRE, incorporating mpMRI (PI-RADS 1-5). The AUC for G ≥ 2 PCa for the developing cohort (n = 231, with a prevalence 25.5%) was 0.93 [0.89-0.96] (p < 0.001) ( Table 2).…”
Section: In Prior Negative Biopsy Settingmentioning
confidence: 99%
“…The accuracy of the systematic biopsy is dependent on the number of cores. Most studies reported a transrectal approach with a median of 12 biopsy cores (Table 1) [20,[22][23][24][25][26][27]30]. However, three studies used a transperineal approach with biopsy cores ranging from 24 to 40 [21,28,29].…”
Section: Considerations and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation